1998
DOI: 10.1016/s0022-2275(20)32514-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein lipase mediates an increase in the selective uptake of high density lipoprotein-associated cholesteryl esters by hepatic cells in culture

Abstract: In this study the effect of lipoprotein lipase (LPL) on the selective uptake of high density lipoprotein (HDL) cholesteryl esters (CE) by hepatic cells was investigated. Human HDL 3 (d 1.125-1.21 g/ml) was radiolabeled with 125 I in the protein moiety and with 3 H in the CE moiety. LPL was prepared from bovine milk. Human hepatocytes in primary culture and human Hep3B hepatoma cells were incubated in medium containing doubly radiolabeled HDL 3 with or without LPL. Without LPL, apparent HDL 3 particle uptake ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…More recently, it has become apparent that LpL has non-enzymatic actions. In this context, LpL, as well as hepatic lipase (34,35), can promote selective uptake of HDL lipid (36). Perhaps in mice containing the MCK-LpL transgene, this action, rather than LpL-mediated lipolysis predominates as the mice have very low levels of VLDL and LpL is not limiting.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has become apparent that LpL has non-enzymatic actions. In this context, LpL, as well as hepatic lipase (34,35), can promote selective uptake of HDL lipid (36). Perhaps in mice containing the MCK-LpL transgene, this action, rather than LpL-mediated lipolysis predominates as the mice have very low levels of VLDL and LpL is not limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, selective cholesteryl ester (CE) uptake may be even more important in mice and other CETP-deficient animals. Recently, LPL has been shown to aid in the selective uptake of HDL-CE by macrophages and hepatic cells (57,58). Thus, in the absence of CETP and apoE, which may also aid in the bridging of lipoproteins to the cell surface (59), a reduction in the amount of LPL protein may compromise the ability of HDL to deliver its CEs to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our report describes a novel non-lipolytic function for lipoprotein-bound LPL that comes in addition to other functions recently described. Several works have indeed demonstrated that LPL may facilitate the interaction of different lipoproteins with various tissues by mechanisms involving heparan sulfate proteoglycans and/or membrane receptors (35)(36)(37)(38)(39)(40)(41)(42). Thus LPL appears now clearly as a protein that exerts multiple functions in lipoprotein metabolism, functions that do not necessarily result from its lipolytic activity.…”
Section: Discussionmentioning
confidence: 99%